Proceedings of the final workshop on "Improvement of environmental education in agricultural sciences" (CTU/JICA, 2002)
Contents: Research on soil and water environment, bio-diversity and genetic resources, study on technology of reducing agrochemical residues in plants in the Mekong Delta.